2014
DOI: 10.1111/jorc.12093
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Care in Advanced Kidney Disease: Patient Attitudes and Expectations

Abstract: SUMMARYTreatment with dialysis has benefitted large numbers of patients with advanced kidney disease. It is though highly intrusive and demanding and some elderly, frail patients may tolerate it poorly. Some of these patients who are either approaching ‘end‐stage’ kidney disease or ‘failing’ despite being on dialysis may choose to pursue supportive or palliative approaches, partially or fully replacing the dialysis option. Here, we describe some of the challenges confronting these patients and present data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In addition, cultural beliefs and attitudes can change over time under the influence of better understanding of what a treatment actually can or cannot achieve [24,25]. In discussions with patients and their relatives, physicians should therefore explain that they believe the treatment does not add qualitative life years and that this fact steers their concern about continuing it [26]. However, many physicians may feel uncomfortable talking about withdrawal with patients [27].…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…In addition, cultural beliefs and attitudes can change over time under the influence of better understanding of what a treatment actually can or cannot achieve [24,25]. In discussions with patients and their relatives, physicians should therefore explain that they believe the treatment does not add qualitative life years and that this fact steers their concern about continuing it [26]. However, many physicians may feel uncomfortable talking about withdrawal with patients [27].…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Prior studies have also shown that in particular the functional status of the elderly haemodialysis patient worsens notably despite treatment of uraemia, especially when significant comorbid conditions were present [7, 38]. On the other hand, there is evidence that an acceptable functional status can be maintained until the very late phase in conservatively managed elderly ESRD patients and that a palliative ‘no dialysis’ approach may be more suitable for a certain subset of patients [39, 40]. Murtagh et al [41`] reported 2-year survival rates of up to 66% for ESRD patients managed without RRT and that functional status declined steeply only in the last month of life.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Canada and the UK suggest that patients wish to plan for the end of their lives and look to their clinicians to initiate discussions at the appropriate time [14, 15]. Most of the patient experience research, however, has excluded non-English speakers and we know little of whether the same is true for people with different cultural backgrounds or about the delivery of their care.…”
Section: Discussionmentioning
confidence: 99%